PENGEMBANGAN PERANGKAT PEMBELAJARAN PBL BERBANTUAN ARTIFICIAL INTELLIGENCE UNTUK MENINGKATKAN KETERAMPILAN PEMECAHAN MASALAH SISWA KELAS IX SEKOLAH INDONESIA JEDDAH - NOVIA ROHMAWATI, RIZKA; Wasis, Wasis; Sunarti, Titin (Jurnal Pendidikan : Riset dan Konseptual, 2026)
This study aims to develop a Problem-Based Learning (PBL) instructional package assisted by Artificial Intelligence (AI) that is valid, practical, and effective in improving the problem-solving skills of ninth-grade students in Natural Science at Sekolah Indonesia Jeddah. The study employed the ADDIE development model, involving 60 students from three classes and four validators comprising two academic experts and two experienced science teachers. Data were collected through expert validation, implementation observation, response questionnaires, and problem-solving skills tests analyzed using the Normalized Gain (N-Gain) formula. The results indicate that the instructional package achieved an average validity score of ≥ 4.43, categorized as highly valid. The implementation rate reached 90%, with positive teacher responses at 100% and student responses at 87%, confirming that the package is highly practical. Regarding effectiveness, the average N-Gain was 0.62 in the moderate category, with 76.7% of students surpassing the minimum competency threshold across all six problem-solving indicators adapted from the PISA 2025 Framework. These findings demonstrate that the integration of PBL with AI-assisted adaptive scaffolding and formative feedback constitutes an effective pedagogical solution for developing students' problem-solving skills in twenty-first-century learning contexts. Keywords: Problem-Based Learning, Artificial Intelligence, Problem-Solving Skills, Alternative Energy, Sekolah Indonesia Jeddah